Association of non-invasive measures of subclinical atherosclerosis and arterial stiffness with mortality and major cardiovascular events in chronic kidney disease: systematic review and meta-analysis of cohort studies - Kouis, Panayiotis; Kousios, Andreas; Kanari, Athina; Kleopa, Daphne; Papatheodorou, Stefania; Panayiotou, Andrie G. (My University, 2020)
Background. Non-invasive cardiovascular disease (CVD) risk prediction, in subclinical stages, aiming to stratify patients and tailor interventions remains an unmet need in chronic kidney disease (CKD). In this meta-analysis, we summarize the association of carotid intima–media thickness (cIMT), coronary artery calcium score (CACS) and pulse wave velocity (PWV) with all-cause mortality, cardiovascular (CV) mortality and CV events in non-dialysis CKD and patients on haemodialysis. Methods. Systematic review and meta-analysis of prospective cohort studies. Results. Out of 27 984 records, a total of 45 studies were eligible for quantitative synthesis; 11 for cIMT, 18 for CACS and 16 for PWV involving 2235, 4904 and 5717 patients, respectively. Meta-analysis was possible from pooled data of five cIMT studies (708 subjects), eight CACS studies (862 subjects) and nine PWV studies (1508 subjects). In dialysis patients, cIMT was associated with all-cause mortality [relative risk (RR) per unit increase: 1.08, 95% confidence interval (CI) 1.00–1.17, I2: 68%] and CV mortality (RR: 1.29, 95% CI 1.14–1.47, I2: 0%). High versus low CACS was associated with all-cause mortality (RR: 2.51, 95% CI 1.66–3.79, I2: 5.7%) and CV events (RR: 3.77 95% CI 2.16–6.58, I2: 20.2%). High versus low PWV was associated with all-cause (RR: 5.34, 95% CI 3.01–9.47, I2: 0%) and CV mortality (RR: 8.55, 95% CI 4.37–16.73, I2: 0%). The combined estimated for all-cause mortality per 1 m/s increment unit in PWV was 1.25 (95% CI 1.17–1.34, I2: 0%) and for CV mortality was 1.24 (95% CI 1.16–1.34, I2: 15.5%). In non-dialysis patients, CACS was associated with CV events (RR: 4.02, 95% CI 1.57–10.29, I2: 63.4%). High versus low PWV was associated with all-cause mortality (RR: 2.52, 95% CI 1.40–4.55, I2: 62.6%). Conclusions. Non-invasive measures of atherosclerosis and arterial stiffening are associated with all-cause and CV mortality as well as CV events among patients with all stages of CKD. These markers could be considered for the evaluation of CV morbidity and mortality risks. Moreover, the results of this meta-analysis support the study of interventions, with effect on these markers of vascular disease, on long-term CVD outcomes.
Keywords: CACS; Cardiovascular risk; CIMT; Haemodialysis; PWV